Quantification model for energy consumption in edification - Mercader, Mª P.; Olivares, M.; Ramírez de Arellano, A. (Materiales de Construcción, 2012)
The research conducted in this paper focuses on the generation of a model for the quantification of energy consumption in building. This is to be done through one of the most relevant environmental impact indicators associated with weight per m2 of construction, as well as the energy consumption resulting from the manufacturing process of materials used in building construction. The practical application of the proposed model on different buildings typologies in Seville, will provide information regarding the building materials, the subsystems and the most relevant construction elements. Hence, we will be able to observe the impact the built surface has on the environment.The results obtained aim to reference the scientific community, providing quantitative data comparable to other types of buildings and geographical areas. Furthermore, it may also allow the analysis and the characterization of feasible solutions to reduce the environmental impact generated by the different materials, subsystems and construction elements commonly used in the different building types defined in this study.